PRECLINICAL HEMOCOMPATIBILITY STUDIES FOR IMPLANTABLE MEDICAL DEVICES: REVIEW AND EXPERIMENTAL RESEARCH RESULTS - M. D. Boyarskiy; Y. V. Tarasov; Y. I. Philippov; N. P. Sachivkina; Ya. M. Stanishevkiy (Разработка и регистрация лекарственных средств, 2019)
Active use of medical devices in contact with the blood stream has created the need to articulate the testing requirements of such products [1], various methods of modelling and assessment of potential complications. One of the most important aspects of testing such products is to evaluate their direct impact on blood. To obtain objective results of the study any modeling should be as close as possible to the situation of clinical use and reproduce the characteristics of blood flow. And also take into account the possibility of the use of anticoagulants and introducing in the model additional pharmacological preparations if they can influence the biochemical and physical characteristics of blood and their use is inextricably linked to the use of the product. The present article contains the results of the conducted scientific-research and experimental-design works on creation of the device to simulate the conditions of the blood flow to the preclinical testing of experimental samples of materials and devices intended for implantation in the human body for permanent or prolonged contact with blood